2017
DOI: 10.1186/s12913-017-2388-8
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Health care by Allocating Resources Effectively (SHARE) 7: supporting staff in evidence-based decision-making, implementation and evaluation in a local healthcare setting

Abstract: BackgroundThis is the seventh in a series of papers reporting Sustainability in Health care by Allocating Resources Effectively (SHARE) in a local healthcare setting. The SHARE Program was a systematic, integrated, evidence-based program for resource allocation within a large Australian health service. It aimed to facilitate proactive use of evidence from research and local data; evidence-based decision-making for resource allocation including disinvestment; and development, implementation and evaluation of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 94 publications
0
22
0
Order By: Relevance
“…More specifically, author co-citation analysis revealed three schools of thought in the SHM literature: (1) sustainable change in health care services, (2) innovations in managing health care operations, and (3) prioritizing and allocating resources for sustainability. The science map of the SHM literature highlighted both the micro-level focus on healthcare management in organizations [11,13,49,63,66], as well as macro-level issues in healthcare systems [70][71][72][73][74][75][76][77].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, author co-citation analysis revealed three schools of thought in the SHM literature: (1) sustainable change in health care services, (2) innovations in managing health care operations, and (3) prioritizing and allocating resources for sustainability. The science map of the SHM literature highlighted both the micro-level focus on healthcare management in organizations [11,13,49,63,66], as well as macro-level issues in healthcare systems [70][71][72][73][74][75][76][77].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Key authors include five Australian scholars: Harris with 77 co-citations [70][71][72][73][74][75][76][77], Allen with 53 co-citations [70][71][72][75][76][77], King with 44 co-citations [70][71][72][75][76][77], Elshaung with 42 co-citations [74,[78][79][80], and Mitton with 42 co-citations [78,81]. Key literature within this School centers on a series of 11 research papers published under the acronym, 'SHARE' or 'Sustainability in health care by allocating resources effectively' [70,[72][73][74][75][76][77][82][83][84]. These papers investigated the process of disinvestment in the Australian health services network using an evidence-based approach.…”
Section: Intellectual Structure Of the Healthcare Management Knowledgmentioning
confidence: 99%
“…Although authors do not use the term "learning health system" in the papers, it is clear that the goal of the project is to create a system that implements evidence, learns from the implementation, and feeds that learning back into the system and larger health care community. 25,64,65 In summary, gaps exist between the needs of health systems and traditional evidence synthesis products in terms of topics covered, formats in which the synthesis is presented, and time for production. Evidence synthesis programs can support health systems by providing rapid, focused and layered summaries, addressing a broad range of topics of relevance to health systems, and by including contextual and operational evidence from local sources when available.…”
Section: The Learning Health System Contextmentioning
confidence: 99%
“…Based on the present findings, most of the previous studies only referred to some part of the components and steps of the EBDM in HSM and neglected the other parts or they were not sufficiently comprehensive (37)(38)(39)(40)(41)(42)(43)(44)(45)(46). However, the findings of each previous study completed some parts of the framework which presented in this study.…”
Section: Discussionmentioning
confidence: 55%
“…The present findings showed that in the fourth main step, "evidence acquisition and integration", the most important sub-step is "finding the sources for seeking the evidence" (35,(45)(46)(47)55,63,65).…”
Section: Inquiringmentioning
confidence: 60%